2012
DOI: 10.1259/bjr/25428720
|View full text |Cite
|
Sign up to set email alerts
|

Volumetric modulated arc therapy planning for distal oesophageal malignancies

Abstract: Objectives: Volumetric modulated arc therapy (VMAT) is a novel form of intensitymodulated radiation therapy that allows the radiation dose to be delivered in a single gantry rotation using conformal or modulated fields. The capability of VMAT to reduce heart and cord dose, while maintaining lung receiving 20 Gy ,20%, was evaluated for chemoradiation for oesophageal cancer. Methods: An optimised forward-planned four-field arrangement was compared with inverse-planned coplanar VMAT arcs with 35 control points fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 44 publications
0
15
0
Order By: Relevance
“…Increasing the low dose region may affect pulmonary function and, subsequently, patients' quality of life and survival . Only a few studies on VMAT for esophageal cancer have been published, mostly focused on dosimetric comparison . No other clinical data has been reported on RP in patients with esophageal cancer treated with VMAT.…”
Section: Discussionmentioning
confidence: 99%
“…Increasing the low dose region may affect pulmonary function and, subsequently, patients' quality of life and survival . Only a few studies on VMAT for esophageal cancer have been published, mostly focused on dosimetric comparison . No other clinical data has been reported on RP in patients with esophageal cancer treated with VMAT.…”
Section: Discussionmentioning
confidence: 99%
“…Benthuysen et al [151] evaluated VMAT in distal oesophageal cancers and found comparable PTV coverage and OAR sparing to fixed field IMRT with a 42-67% reduction in MU, but greater low dose radiation to the body (V5 Gy 18% greater for VMAT plans). Hawkins et al [152] compared VMAT with 4-field CRT in 10 patient datasets with locally advanced or inoperable distal oesophageal cancers. They found improved OAR sparing (V30 Gy to heart 31% vs 55%) and improved PTV conformity with VMAT.…”
Section: Intra-abdominal Tumoursmentioning
confidence: 99%
“…The prescribed dose was 54 Gy in 30 fractions and the technical details of the plans were otherwise as for the lung cases, and following our clinical practice. 36 The three prostate plans were created by copying the PTV, rectum, bladder, bowel, and femoral head volumes from three patients whose prostate and seminal vesicles had previously been treated using the PACE (Prostate Advances in Comparative Evidence) protocol, 37 onto a Solid Water phantom of dimensions 30 cm wide × 30 cm long × 20 cm high. The isocenter was located at the center of the phantom and the three volumes were prescribed to 78 Gy in 39 fractions.…”
Section: C Vmat Dosimetrymentioning
confidence: 99%